Diastereoselective Synthesis and Diversification of Highly Functionalized Cyclopentanones - Baumann, Marcus; Baxendale, Ian R. (Synthesis, 2018)
An efficient entry into highly substituted cyclopentanones is presented based on functionalizing cyclopentenones by means of an aza-Michael reaction with different aniline nucleophiles. The excellent diastereoselectivity of this process is ascribed to H-bonding between a tertiary alcohol and the incoming nucleophiles. Additionally, the functionalization of the parent cyclopentenones via the Baylis–Hillman reaction is demonstrated. Together, these transformations showcase the elaboration of a simple precursor by installation of versatile functionalities at either the α- or β-position of the embedded enone and thus represent valuable methods for the construction of diversely functionalized cyclopentanones.
Keywords: cyclopentanone; aza-Michael reaction; Baylis–Hillman reaction; diastereoselectivity; H-bonding